HUBUNGAN KARAKTERISTIK INDIVIDU DAN IKLIM KERJA DENGAN KELUHAN MSDs PADA PEKERJA PERAKITAN MINI BUS DI PT MEKAR ARMADA JAYA MAGELANG - Komarul Fausiyah (Universitas Airlangga, 2017)
Musculoskeletal disorders (MSDs) are disturbances in the skeletal muscles that affect workers, ranging from mild to very severe complaints. MSDs complaints can be caused by internal factor such as gender, age, years of employement, smoking habit and external factor such as exposure to hot work climates. These was an analytical-observational study with a cross-sectional approach. The research samples consisted of 65 workers. Samples were selected by simple random sampling. Individual characteristics data collected by questionnaire, work climates data were obtained by Wet Bulb Globe Temperature (WBGT) measurement and MSDs complaints data were analyzed by Nordic Body Map (NBM). All data were analyzed by the Spearman-rho correlation with a significance level of α = 0.05. Results showed that most of workers had a moderate risk of MSDs complaints (55.4%). Based on WBGT measurement, work climate exceeded the Threshold Limit Value (TLV). There were no correlation between MSDs complaints and workers characteristics (age, years of employment, and smoking habits). However, there was a significant correlation between MSDs complaints and work climate (p = 0.000; r = 0.730). The company are advised to redesign natural and artificial ventilation system, increasing the knowledge of all workers about ergonomic risks prevention based on their activities, reduce the health effects of workers smoking habit by regular exercise every day and set time of job rotation for 5-15 minutes/hour for workers do other work with a lighter workload. Keywords: individual characteristics, work climate, MSDs complaints